St. peter's fair eaudiobook - Peters, Ellis (The Chronicles of Brother Cadfael, 2014)
An opportunity to put aside the horrors of war is dashed when bodies begin to pile up at St. Peter's Fair St. Peter's Fair is a grand, festive event, attracting merchants from across England and beyond. There is a pause in the civil war racking the country in the summer of 1139, and the fair promises to bring some much-needed gaiety to the town of Shrewsbury—until the body of a wealthy merchant is found murdered in the river Severn. Was Thomas of Bristol the victim of murderous thieves? And, if so, why were his valuables abandoned nearby? Brother Cadfael, that shrewd but kindly monk, offers to help the merchant's lovely niece Emma. But while he is searching for the killer, Thomas of Bristol's wares are ransacked and two more men are murdered. Emma almost certainly knows more than she is telling—as others will soon realize. Cadfael desperately races to save the young girl, knowing that in a country at war with itself, betrayal can come from any direction, and even good intentions can kill.